The nonsynaptic plasticity in Parkinson’s disease: Insights from an animal model - Viegas, Mônica P.C.; Santos, Luiz E.C.; Aarão, Mayra C.; Cecilio, Samyra G.; Scorza, Carla A.; Moret, Marcelo A.; Finsterer, Josef; Scorza , Fulvio A.; Almeida, Antônio-Carlos G.; Medrado, Joana M.; Pires, Arthur C.; Rodrigues, Antônio M. (Clinics, 2023)
Background:The 6-OHDA nigro-striatal lesion model has already been related to disorders in the excitability and synchronicity of neural networks and variation in the expression of transmembrane proteins that control intra and extracellular ionic concentrations, such as cation-chloride cotransporters (NKCC1 and KCC2) and Na+/K+-ATPase and, also, to the glial proliferation after injury. All these non-synaptic mechanisms have already been related to neuronal injury and hyper-synchronism processes.Objective:The main objective of this study is to verify whether mechanisms not directly related to synaptic neurotransmission could be involved in the modulation of nigrostriatal pathways. Methods: Male Wistar rats, 3 months old, were submitted to a unilateral injection of 24 µg of 6-OHDA, in the striatum (n= 8). The animals in the Control group (n= 8) were submitted to the same protocol, with the replacement of 6-OHDA by 0.9% saline. The analysis by optical densitometry was performed to quantify the immunoreactivity intensity of GFAP, NKCC1, KCC2, Na+/K+-ATPase, TH and Cx36. Results: The 6-OHDA induced lesions in the striatum, were not followed by changes in the expression cation-chloride cotransporters and Na+/K+-ATPase, but with astrocytic reactivity in the lesioned and adjacent regions of the nigrostriatal. Moreover, the dopaminergic degeneration caused by 6-OHDA is followed by changes in the expression of connexin-36. Conclusions: The use of the GJ blockers directly along the nigrostriatal pathways to control PD motor symptoms is conjectured. Electrophysiology of the striatum and the substantia nigra, to verify changes in neuronal synchronism, comparing brain slices of control animals and experimental models of PD, is needed.